Subacute sclerosing panencephalitis in a child with celiac disease – A rare association - Singh, Aaradhana; Garg, Neha; Bagaria, Anjali; Aggarwal, Anju; Narang, Manish (Indian Journal of Child Health, 2019)
Celiac disease (CD) is an immune-mediated disease with varied intestinal and extraintestinal manifestations. Among extraintestinal manifestations, neurological conditions are being reported with increased frequency nowadays. We report a child of CD with progressively increasing dementia, poor scholastic performance, and myoclonic epilepsy. On further investigation, the cause of neurological manifestations was diagnosed as subacute sclerosing panencephalitis (SSPE). It is a slowly progressive neurodegenerative disorder caused by defective measles virus which is eventually fatal. The coexistence of CD and SSPE could not be found in literature.